Response of late-sown gram (Cicer arietinum) to irrigation and phosphorus - YADAV, S K; CHANDER, KRISHAN; KUMAR, ASHOK (The Indian Journal of Agricultural Sciences, 2013)
Response of late-sown gram or chickpea (Cicer arielinum L.) to 4 levels of irrigation (no post-sowing irrigation, Post-sowing irrigation at irrigation depth: cumulative pan-evaporation ratios 0.2, 0.4 and 0.6) and phosphorus (0, 8.8, 17.6 and 26.4 kg P/ha) was investigated at Hisarin the winter seasons of 1986-87 . and 1987-88. The unirrigated plants had lower leaf-water potential, evapo-transpiration, stomatal conductance, light absorption, leaf -area index, yield components and grain yield compared with irrigated plants, but had higher canopy temperature. Among yield components, water stress primarily affected the number of pods/m row length and had litile effect on grains/pod. P application improved the leaf-water potential, stomatal conductance,light absorption,leaf-area index, seed yield and water-use efficiency and decreased the canopy temperature. The combination of irrigation water: cumulative pan-evaporation ratio 0.4 with 26.4 kg/ha gave significantly higher grain yield than other treatments.